Activated carbon nanotube/polyacrylic acid/stearyl alcohol nanocomposites as thermal energy storage effective shape-stabilized phase change materials - Goksu, Haydar; Aydinli, Elif; Hekimoglu, Gokhan; Sari, Ahmet; Gençel, Osman; Subasi, Serkan; Tozluoglu, Ayhan; Gençel, Osman (Elsevier, 2022)
Stearyl alcohol (SA) as one of organic phase change materials (PCMs) has promising thermal energy storage prospective. However, the leakage issue during solid-liquid phase change period and low heat harvesting and releasing rate significantly attenuates its TES potential. Towards to overcome these drawbacks, the SA was shape stabilized using the cross-linked poly acrylic acid (PAA) and activated single walled carbon nanotubes (aSWCNTs) at three different weigh ratio of 1:1:2, 1:3:4 and 1:5:6 (a-SWCNTs:PAA:SA). The chemical/crystalline and morphologic structures of the produced shape stabilized-nano composite PCMs (SS-NCPCMs) were investigated by FT-IR, XRD and SEM analyses. The latent heat storage (LHS) features and thermal stability of the SSNCPCMs were measured by DSC and TGA techniques. The thermal cycling effect on the LHS properties and chemical structures of the SS-NCPCMs was also estimated. The DSC findings indicated that the SS-NCPCMs had melting temperature of around 55-56 C and latent heat capacity of about 135 J/g. TGA measurements disclosed that the thermal degradation temperatures of the nano composite PCMs were prolonged somewhat compared to the SA. A 500 heating-cooling cycling test revealed that the SS-NCPCMs had great chemical and LHS stability. The heat harvesting and releasing performance of the NCPCMs were considerably shortened compared to those of pure SA. The obtained results exposed that the synthesized SWCNTs/PAA/SA composites can be evaluated as promising LHS materials for thermal management of electronic systems, automobile modules, food carriers, solar PV panels etc.
Keywords: Poly Acrylic Acid; Swcnts; Stearyl Alcohol; Pcm; Latent Heat; Thermal Energy Storage; Heat Harvesting And Releasing Performance